Establishing the relationship between familial dysbetalipoproteinemia and genetic variants in the APOE gene. Issue 4 (22nd August 2022) - Heidemann, Britt E.; Koopal, Charlotte; Baass, Alexis; Defesche, Joep C.; Zuurbier, Linda; Mulder, Monique T.; Roeters van Lennep, Jeanine E.; Riksen, Niels P.; Boot, Christopher; Marais, A. David; Visseren, Frank L. J.
Abstract: Familial Dysbetalipoproteinemia (FD) is the second most common monogenic dyslipidemia and is associated with a very high cardiovascular risk due to cholesterol‐enriched remnant lipoproteins. FD is usually caused by a recessively inherited variant in the APOE gene (ε2ε2), but variants with dominant inheritance have also been described. The typical dysbetalipoproteinemia phenotype has a delayed onset and requires a metabolic hit. Therefore, the diagnosis of FD should be made by demonstrating both the genotype and dysbetalipoproteinemia phenotype. Next Generation Sequencing is becoming more widely available and can reveal variants in the APOE gene for which the relation with FD is unknown or uncertain. In this article, two approaches are presented to ascertain the relationship of a new variant in the APOE gene with FD. The comprehensive approach consists of determining the pathogenicity of the variant and its causal relationship with FD by confirming a dysbetalipoproteinemia phenotype, and performing in vitro functional tests and, optionally, in vivo postprandial clearance studies. When this is not feasible, a second, pragmatic approach within reach of clinical practice can be followed for individual patients to make decisions on treatment, follow‐up, and family counseling. Abstract :